Analisis Sebaran Spasial Penggunaan Lahan dan Kesesuaian Lahan Daerah Aliran Sungai Menggunakan Data Penginderaan Jauh dan Sistem Informasi Geografis - Nining Erlianti; La Harudu; Tahir Tahir; Andrias Andrias (Jurusan Pendidikan Geografi FKIP Universitas Halu Oleo, 2025)
Utilizing remote sensing data and Geographic Information Systems to analyze the spatial distribution of watershed land use is one way to prepare land use designations. This research aims to determine the distribution and suitability of land use in the Wanggu River Basin Zone South Konawe Regency. The method used in this research uses a survey method with supervised classification. The research results obtained eight land use classes, namely, empty land, residential areas, water bodies, shrubs, rice fields, plantations, ponds and forests. The results of the analysis showed that the pond land use class had the smallest percentage, namely 1.09%, while the land use class had the lowest percentage. high, namely forest with a percentage of 64.01%. Based on the accuracy test with the confusion matrix, the accuracy of the Landsat-8 imagery interpretation results was 86.63%. The watershed land use is appropriate and the interpretation results are in the good category, so that land suitability in the Wanggu watershed is more dominant in suitable land with an area of ​​43,776.96 ha or 67.58%, than unsuitable land with an area of ​​20,764.79 ha or 32.42%.